Reconstruction of Chronic Injured Distal Tibiofibular Syndesmosis with Autogenous Tendon Graft: A Systematic Review. (1st February 2021) - Xu, Han-Lin; Song, Yu-Jie; Hua, Ying-Hui
Abstract : Background . Chronic injuries of the distal tibiofibular syndesmosis are common in patients who fail to receive adequate diagnosis and timely treatment. Reconstruction of the distal tibiofibular syndesmosis with an autogenous tendon graft in these patients is effective, although relatively rarely reported. Purpose . To investigate clinical outcomes of syndesmosis reconstruction with an autogenous tendon graft for chronic injuries of the distal tibiofibular syndesmosis by reviewing the current literature. Methods . An English literature search was conducted in the MEDLINE, CENTRAL, and Cochrane databases to identify published studies up to October 2017. Preset inclusion and exclusion criteria were applied to identify all eligible articles. Results . Five studies (all with level IV evidence) that included a total of 51 patients who underwent reconstruction with an autogenous tendon graft were identified. It was reported that the symptoms were relieved postoperatively, including obviously improved functional outcomes and restoration of motions and exercise capacity. The mean American Orthopedic Foot and Ankle Society scale score of 16 patients was 53 preoperatively and 89 postoperatively. The visual analogue scale score of 14 patients decreased from 82.4 preoperatively to 12.6 postoperatively. A total of 5 (9.8%) complication cases were reported. Conclusion . Reconstruction of the distal tibiofibular syndesmosis with an autogenous tendon for chronic syndesmosis injury showed a good therapeutic effect in terms of both subjective symptoms and objective evaluation scores. The interosseous ligament could be an appropriate reconstruction target in the treatment of chronic syndesmosis injury.